beta-Lactamase-mediated inactivation and efficacy of cefazolin and cefmetazole in Staphylococcus aureus abscesses. - Fields, M T (1993)
12694668 Clinical reports and animal models have demonstrated that cefazolin may have decreased efficacy against some strains of Staphylococcus aureus because of type A beta-lactamase-mediated hydrolysis. We sought to measure biologically active cefazolin concentrations within abscesses with high concentrations of S. aureus and compare the concentrations with those of cefmetazole, a beta-lactamase-stable cephamycin. A type A beta-lactamase-producing strain of S. aureus with a demonstrated inoculum effect against cefazolin (MIC at an inoculum of 5 x 10(5) CFU/ml, 1.0 micrograms/ml; MIC at an inoculum of 5 x 10(7) CFU/ml, 32.0 micrograms/ml) but not cefmetazole (MICs at inocula of 5 x 10(5) and 5 x 10(7) CFU/ml, 2.0 micrograms/ml) was used. Cefazolin or cefmetazole (100 mg/kg of body weight every 8 h for 8 days) was administered to rabbits with infected tissue cages. No differences in the concentrations of the two drugs in the uninfected tissue cages were observed. Higher concentrations of cefmetazole than cefazolin were found in infected tissue cages at day 3 (5.9 +/- 0.7 versus 2.2 +/- 0.3 micrograms/ml; P < 0.01), day 5 (9.1 +/- 2.6 versus 3.6 +/- 0.7 micrograms/ml; P = 0.02), and day 8 (9.4 +/- 1.4 versus 4.8 +/- 0.9 micrograms/ml; P = 0.01) after infection. Cefazolin and cefmetazole were equally effective in reducing the bacterial concentration in the abscess. In vitro experiments demonstrated greater cefazolin than cefmetazole degradation by S. aureus, but the differences were greater in serum than in abscess fluid supernatants. We conclude that abscess cefazolin concentrations are diminished by type A beta-lactamase-producing S. aureus, but this did not affect drug efficacy in this model.